Performance of electrospun polystyrene membranes in synthetic produced industrial water using direct-contact membrane distillation - Haneen Abdelrazeq (16931823) (2020)
Desalination of produced water in the gulf petrochemical industry is a continuing challenge to major research groups in the field. With a focus on produced water from desalination plants, it has become crucial to define and follow specific protocol in wastewater purification technologies. In this work, an optimized guideline for direct contact membrane distillation (DCMD) was developed and implemented. A bench-scale DCMD unit was performed under optimum process parameters of feed and distillation inlet temperatures of TFeed = 60 ◦C and TDist = 20 ◦C, respectively. A low flow rate of 0.03 L/min was used to avoid wetting of the fabricated membrane. A hydrophobic polystyrene flat sheet was prepared in the labs using a custom-made electrospinning apparatus. The effect of varying concentrations on the hydrophobic polystyrene membrane was studied using a high concentration brine feed (C1 ≈ 75,500 ppm) and another feed of lower concentration (C2 ≈ 25,200 ppm). A high salt rejection rate of 99% was achieved. The morphological structure, pore size and fiber length was analyzed using SEM. Conductivity measurements have confirmed an improved permeate quality of 99%. Thus, as per the DCMD performance of the polystyrene membrane, the generated permeate indicates that the membrane performance may have scalable potential contribution to industrial wastewater purification. Other Information Published in: Desalination License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.desal.2020.114663